Pengaruh Pemberian Mikro Organisme Lokal (MOL) Bonggol Pisang terhadap Pertumbuhan Stum Mata Tidur Karet (Hevea brasiliensis muell. Arg) Klon IRR 112 di Pollybag: The Effect of Giving Local Micro-Organisms (MOL) Banana Weevil on the Growth of Rubber Sleep Eye Stum (Hevea brasiliensis Muell. Arg) IRR 112 clone in Polybag - Rusnaini Rusnaini; Syahid Ali Ackbar (Politeknik Negeri Lampung, 2022)
This study aimed to examine the effect of local microorganism (MOL) administration of banana weeds on the growth of rubber bed eye stumps (Hevea brasiliensis muell. Arg.) IRR 112 clone in polybags. The research was conducted in Sembawa Village, Sembawa District, Banyuasin Regency, South Sumatra. The time of the research was started from January to April 2019. The research design used was a Randomized Block Design (RAK), there were 6 treatments, namely P0 = 0% (Control); P1 = 10%; P2 = 20%; P3 = 30%; P4 = 40%; and P5 = 50% and 4. Each treatment consisted of 6 plants, so the number of plants studied was 96 plants (polybags). Each experimental treatment unit uses 2 sample plants. The research data were analyzed by analysis of variance followed by the BNJ test if the effect of treatment was real or very real. The observed variables were: shoot emergence (HST), shoot height (cm), shoot diameter (cm), number of leaves (strands) and root dry weight (g). Based on the results of research that has been carried out, it was concluded that the application of MOL banana weevil did not significantly affect the time of shoot height, shoot diameter, number of leaves, but had a significant effect on the time of shoot emergence and had a very significant effect on root dry weight. Treatment with 30% banana weevil MOL concentration tended to give the best results for shoots appearing 3.66 days after planting, shoot height 28.31 cm, stem diameter 0.375 cm, number of leaves 12.50 strands and root dry weight 2.29 g.